Palladium (II) chloride (PdCl2) spectrophotometry to determine lipoic acid concentration in plasma and leukocytes - Novian Agni Yudhaswara; Ani Retno Prijanti; Mohamad Sadikin (Acta Biochimica Indonesiana, 2020)
Background: Lipoic acid is a substance contained in intra and extracellular that act as a coenzyme of Pyruvate Dehydrogenase, also as an antidote, chelating agent and antioxidant. Measurement of lipoic acid is needed to determine the amount of lipoic acid that performs its functions either as a coenzyme or an antioxidant. Besides, this measurement requires a special tool such as High Performance Liquid Chromatography (HPLC) and a process that is available in rural or simple laboratories. Objective: A common and easy tool such as a spectrophotometer was conducted and could expected to be a tool of lipoic acid determination in body fluid such as plasma. Methods: Measurement of lipoic acid using spectrophotometry with UV methanol and visible PdCl2 has been tested and compared to HPLC measurement that was valid and reliable in drug measurement or pharmaceutical preparations. Results: Determination of lipoic acid in plasma and leukocytes using PdCl2 produced replicable, reliability and valid result, with high accuracy, precision and was not different from lipoic acid measurement using HPLC, p=0.99. While UV methanol was different compare to HPLC p =0.0001 or was not valid. Conclusion: The measurement of lipoic acid using PdCl2 visible method can be applied to determine the levels of lipoic acid (LA) and DHLA in plasma and equal to HPLC result.